2017
DOI: 10.4102/ojvr.v84i1.1302
|View full text |Cite
|
Sign up to set email alerts
|

Parasites of domestic and wild animals in South Africa. L. Ixodid ticks infesting horses and donkeys

Abstract: The aim of the study was to determine the species spectrum of ixodid ticks that infest horses and donkeys in South Africa and to identify those species that act as vectors of disease to domestic livestock. Ticks were collected opportunistically from 391 horses countrywide by their owners or grooms, or by veterinary students and staff at the Faculty of Veterinary Science, University of Pretoria. Ticks were also collected from 76 donkeys in Limpopo Province, 2 in Gauteng Province and 1 in North West province. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
57
0
1

Year Published

2017
2017
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(66 citation statements)
references
References 12 publications
8
57
0
1
Order By: Relevance
“…The numbers collected from individual animals were generally low and with some exceptions the prevalence of infestation low. The recorded infestation rates are well below those reported in other parts of southern Africa (e.g., Horak et al, 2000), but are consistent with those previously reported in our study area (e.g., Horak et al, 1992). …”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The numbers collected from individual animals were generally low and with some exceptions the prevalence of infestation low. The recorded infestation rates are well below those reported in other parts of southern Africa (e.g., Horak et al, 2000), but are consistent with those previously reported in our study area (e.g., Horak et al, 1992). …”
Section: Resultssupporting
confidence: 93%
“…However, several collections have been made from domestic dogs and some from domestic cats and caracals (Horak and Matthee, 2003, Horak et al, 2010, Matthee et al, 2010). Walker et al (2000) plot locality records across Namibia and south-central South Africa.…”
Section: Resultsmentioning
confidence: 99%
“…Basson et al (1970) found 5% prevalence in the buffaloes they examined. Among the 52 warthogs examined, eight were positive, corresponding to a prevalence of 15.4% (Horak, 1978). Antelope, bush pigs and warthogs can also serve as intermediate host, depending on the presence or absence of carnivore to avoid a break in the life cycle.…”
Section: Zoonotic Cestodes Of Wildlifementioning
confidence: 99%
“…Various wild and domestic carnivores are the preferred hosts of the adults of H. elliptica, including domestic dogs and cats as well as lions (Panthera leo), leopards (Panthera pardus) and cheetahs (Apanaskevich et al, 2007;Horak et al, 1987;Horak et al, 2000;Horak and Matthee, 2003;Horak et al, 2010). Several murid rodent species are the preferred hosts of its immature stages (Hoogstraal, 1956;Horak et al, 2005;Petney et al, 2004).…”
Section: A Hebraeummentioning
confidence: 99%
“…Among domestic animals, the adult ticks primarily parasitise cattle and dogs Walker et al, 2000), but they have also been recovered from many wild animals including felids (Horak et al, 1983;Horak et al, 1987;Horak et al, 2000;Norval and Mason, 1981). The immature stages prefer murid rodents as hosts, some species of which may be burrow-dwelling (Braack et al, 1996;Hoogstraal, 1956;Norval and Mason, 1981).…”
Section: A Hebraeummentioning
confidence: 99%